Parent Experiences Caring for a Child With Bronchiolitis: A Qualitative Study. (December 2020) - Campbell, Alyson; Hartling, Lisa; Louie-Poon, Samantha; Scott, Shannon D
Background: Bronchiolitis is an acute lower respiratory infection, with significant impacts on children and families and strains on the health care system. Understanding parents' experiences and information needs caring for a child with bronchiolitis is crucial to highlight misconceptions or issues contributing to the high burden. The objective of this qualitative study was to describe parents' experiences caring for a child with bronchiolitis. Methods: Qualitative description guided this study. Participants were recruited from the Stollery Children's Hospital emergency department (ED), a specialized pediatric ED in a major Canadian urban center. Semi-structured interviews were conducted with 15 parents. Results: Five major themes were identified: (a) their children's symptoms and behaviors, (b) bronchiolitis affects the entire family, (c) factors influencing parent's decision to go to ED, (d) ED experience for parents and their children, and (e) bronchiolitis treatment and management. Interviews revealed bronchiolitis has significant effects on both children and families and parents are generally unaware of bronchiolitis symptoms, treatment, and management. Conclusions: Our study highlights that parents have knowledge deficits when it comes to recognizing the presence and severity of bronchiolitis symptoms. Parents would benefit from having more evidence-based resources to enhance their knowledge about the nature of bronchiolitis.